Procedure notes: in the middle of earth powder layers (Palíndromo, 2023)
In this visual essay, I present a sequence of photographs and a list of words, which make up the series No surroundings No contouring. Potentialized by thinking and giving plasticity to singular contexts, in procedures involved with “dust-earth”, and signifiers. In production processes (collecting, photographing and annotating), with the means (listing, classifying and ordering) and continuity (laying out, exposing and collecting produced objects), in the form of procedural notes. Conceived with Vila-Matas, Coccia and Maciel, this essay results in possible readings that culminate in experiences that do not end, in the midst of walking, traces, delicacies and layers of dust-earth.
Keywords: Procedural Notes; To walk; Dust-Earth; Collection